The structure of a novel long-period superlattice phase in Mg97Zn1Yb2 alloys. (June 2018) - Fujita, N.; Matsushita, M.; Tsukamoto, R.; Yamasaki, M.; Kawamura, Y.; Irifune, T.; Abe, E.
Abstract: The second example of a novel long-period superlattcie (LPSL) phase has been discovered in Mg97 Zn1 Yb2 alloys synthesized under high pressure (5 GPa) and at high temperature (673 K), whose superlattice dimensions are described as √3 ×  √ 3 × 2 with respect to the original hexagonal close-packed Mg structure. A model structure is constructed based on atomic-resolution electron microscopy and first-principles calculations, finding that the present LPSL structure is a long-range crystalline ordered version of the isolated Guinier-Preston-type zones reported in conventional age-hardening Mg-Zn-Gd alloys. Therefore, the present LPSL phase could be potentially stable configurations even under ambient conditions and hence formed for broad Mg alloys. Graphical abstract: Unlabelled Image